Avaliação da viabilidade de cateter epidural totalmente implantado em equídeos - Coelho, Cássia Maria Molinaro [UNESP] (2014)
Long term spinal analgesia typically performed in patients suffering from chronic pain or acute painful conditions with high chronicity. Although the horses are commonly affected by disorders that justify the use of this technique, it is observed that the use of spinal catheters is almost exclusively to research purposes, especially because the proximal end of the catheter remain externalized, which requires an intensive care and animal's movement restrictions. Facing this challenge, this study developed a technique to implant an epidural port-a-cath system in horses and donkey, aiming long term epidural patency in animals kept in paddocks and without intensive care. Ten horses and six donkeys were selected in which a polyurethane epidural catheter was implanted through elliptical incision in the sacrococcygeal region. The proximal end catheter was transposed to the gluteal region and connected to the port, buried in this area. After implantation the animals were kept in individual stall on average 20 days and then were housed in collective paddocks whereas remained with the catheter implanted for 8 to 14 months. The percutaneous administrations were well tolerated and the patency still viable, excepting two donkeys. None animal showed behavioral or physiological alterations caused by the surgery procedure or the catheter permanence. Two horses had transient leakage through the port and 5/6 donkeys developed skin ulcers on the port, complications that not did prevent the use of the device. Considering these results, it was concluded that the epidural port-cath system implantation technique is feasible for equine and asinine species and the system was able to maintain a prolonged epidural patency without nosocomial infections and intensive care, which allows the use for research purposes and in patients with painful conditions